The Social Information Processing Model as a Framework for Explaining Frequent Aggression in Adults with Mild to Moderate Intellectual Disabilities: A Systematic Review of the Evidence. Issue 5 (8th August 2013) - Larkin, Peter; Jahoda, Andrew; MacMahon, Ken
<x xml:space="preserve">Abstract</x> Background There is an established evidence base con‐cerning the use of anger management interventions with violent offenders who have intellectual disabilities. However, there has been limited research investigating the role of social cognitive factors underpinning problems of aggression. Psychosocial sources of agg‐ression in the non‐disabled population are generally discussed using Social Information Processing (SIP) models. Method A systematic review of the available evidence was carried out to establish whether SIP offers a useful explanatory model for understanding the contribution of social cognitive factors to problems of aggression presented by people with intellectual disabilities. Results and conclusions Whilst research relating to the SIP model remains sparse for this population, there was evidence for different patterns of processing between aggressive and non‐aggressive individuals. Group diff‐erences included interpretation of emotional cues, inter‐personal attributions and beliefs about the outcomes of aggressive behaviour. The future direction of SIP research with people who have intellectual disabilities is discussed, along with the possibility of using this framework to help build on current initiatives to develop individually tailored interventions to work at a cognitive level with those who are aggressive and offend.